Analysing the southern area of Lake Tana Biosphere Reserve as a tourist destination using the TALC approach - Endalew Tegegne; Dawit Melak; Abebe Lake; Marius-Cristian Tătar; Meron Tenaw Zeleke; Corina-Florina Tătar (UTMS Journal of Economics, 2022)
Ethiopia holds all the necessary ingredients for tourism development, given the multitude and uniqueness of attractions. Among them stands Lake Tana, a UNESCO Biosphere Reserve which is an extremely important resource for Ethiopia, locking up half of its freshwater. The target of the current paper is to make a supply analysis of the southern area of Lake Tana's visitor attractions, accommodation and food and beverage and the accessibility to these attractions as well as to settle the tourism development stage according to the tourism area cycle stage. The Lake Tana visitation trends followed an ascending pattern, figures show domestic tourism as being the most prevalent. The southern part of Lake Tana accounts for 28,3% of the tourist supply when compared to the entire lake's potential, among which the food and beverage sector is the most prevalent. By using the TALC approach, it came out that Lake Tana as a destination is situated on the development stage.
Keywords: Q26; L83; 330; visitor attractions; accommodation analysis; food and beverage sector; tourist flow; tourism area life cycle